Health Education tentang kewaspadaan terjadinya Congestive Heart Failure - Febrianti, Nur; Kadang, Yulta; R, Rosita (PT.Mantaya Idea Batara, 2023)
Heart disease is still a threat in Indonesia and even in the world, one of which is congestive heart failure. congestive heart failure is a type of heart failure that requires timely medical attention. Besides that, community service is one of the duties of lecturers in carrying out the Tri dharma of higher education. The purpose of this community service is to increase public knowledge about awareness of the occurrence of congestive heart failure. The counseling method uses Flip chart and Leaflet media. As a result of the service, the community came at the appointed time, listened to the presenters seriously and during the question and answer session, many people asked questions. In the evaluation session, the community can answer according to the material provided. The conclusion of community service activities has been carried out. The community welcomes the Justitia nursing academy very well and it is hoped that the community will be aware of congestive heart failure, and this community service activity can be carried out on a scheduled basis in Enu village, Donggala district.